KEABSAHAAN SERTIPIKAT HAK MILIK ATAS TANAH BERDASARKAN UUPA DAN PERATURAN PEMERINTAH NOMOR 24 TAHUN 1997 TENTANG PENDAFTARAN TANAH - Emerlanda Leticia; Hasni Hasni (Fakultas Hukum Universitas Tarumanagara, 2019)
The certificate is a proof of ownership that is strong, this certificate comes from land rights which are the right to use and exploit the land which it occupies. Rights to land are also divided into Property Rights, Cultivation Rights, Building Use Rights, Use Rights, Rental Rights for Buildings, Use Rights and Temporary Land Rights. In this case the author will only explain the ownership rights related to legal issues, namely the right of ownership. Property rights are the strongest and most complete rights that humans can have. This right is obtained based on land registration. Own land registration is carried out by the authorized party, namely the National Land Agency. But in this case on the island of Pari, the certificate was declared maladministration by the ORI which caused the author to write about the validity of the certificate of land ownership based on law. With the formulation of the problem, how is the validity of the Certificate of Property Ownership according to uupa and Government Regulation Number 24 of 1997 related to the statement of maladministration by the ORI? and What are the legal consequences for certificate holders due to the administrative maladministration? By using explanatory research methods. In this case the researcher gets the result that in the process of land registration the measurement process is not carried out which is one of the requirements to obtain physical data and there is no announcements must be made because to provide an opportunity to file an objection.